Peran Pendampingan Suami Terhadap Kecemasan Pada Ibu Primigravida Menghadapi Persalinan Di Puskesmas Pattoppakang : The Role of Husband's Accompanying Towards Anxiety in Primigravida Mothers Facing Birth at The Health Center Pattoppakang - Dewi, Dewi; Nuryana, Riska; Sumarmi, Sumarmi; Mantasia, Mantasia (Jurnal Keperawatan Muhammadiyah, 2024)
Introduction of the research is to determine the role of husband's assistance on anxiety among primigravida mothers facing childbirth at the Pattopakang Community Health Center, Takalar Regency in 2023. The research is descriptive correlational research. This research was conducted in the Pattoppakang Community Health Center, Takalar Regency with a population of 30 people and a sample of 30 people. The sample collection technique used was total sampling. The independent variable is husband's assistance. The dependent variable is anxiety in post partum mothers. Data was collected using a questionnaire sheet. Data processing uses Editing, Coding, Scoring, Tabulating and statistical tests use the chi-square statistical test. Results are presented in the form of tables and narratives. The results of this study show that of the 30 respondents, there were 10 respondents who were accompanied and 20 respondents who were not accompanied, with the level of anxiety of the 10 respondents there was 1 respondent who experienced anxiety and 9 of them were not anxious, while of the 20 respondents who were not accompanied there were 8 respondents who did not feel anxious. while 12 others experienced anxiety. The chi square statistical test shows that the p value = 0.015<a (0.05) so that H1 is accepted. The conclusion is that there is a relationship between husband's assistance and anxiety in primigravida mothers facing childbirth. It is recommended that the management of the health center provide counseling or direction to husbands whose wives are pregnant about the importance of the husband's role in accompanying his wife during the birth process.